(untitled) (Asian Journal of Applied Sciences, 2014)
Ten different fungal strains belonging to filamentous fungi were evaluated for their abilities to produce lipid. An oleaginous fungus strain Trichoderma viride-314 was grown the fastest and gave comparable high lipid content up to 20 %. Culture conditions were optimized for oil production by the above fungus in the medium supplemented with different carbon sources, different concentrations of the best carbon source, different pH, temperature and incubation period. The experimental results showed that PD liquid nutrient medium supported relatively lipid accumulation with 50 g L-1 for dextrose concentration at the fifth day of growth. Neither yeast extract nor sugar cane molasses supplement exhibits any significant effects on lipid production. In addition, 28°C, 5.0, static conditions were the favorable for growth temperature, pH value of cultivation medium, respectively. The GC/Ms analysis indicated that the n-hexane lipid fraction of T. viride was mainly composed of 30.01% Palmitoleic acid (C16:1), 23% Linoleic Acid (C18:2), 13% Linolenic acid (C18:3) and about 8% Erucic acid (C22:1). Furthermore, the GC analysis also showed that the total saturated fatty acids represented 8.3% while the value of the total unsaturated was 81.74%. These results giving possibility to use such this fungus strain to produce SCO in a low cost medium from economic point of view.